2016
DOI: 10.21859/eulawrev-08063
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of entrepreneurship education in developing entrepreneurial intentions among Malaysian university students: (a research findings on the structural equation modeling)

Abstract: he current rate of unemployment among graduates in Malaysia has initiated the Malaysian government to look into entrepreneurship as a possible solution and this has led to the introduction of entrepreneurship education in most of the higher educational institutions. The research topic is, 'Effectiveness of entrepreneurship education in developing entrepreneurial intentions among the Malaysian university students'. A theoretical framework has been proposed to identify the research issues and gaps. The research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Accordingly, the position of both entrepreneurial motivation and entrepreneurial attitude is mediating variables that mediate between entrepreneurship education and entrepreneurial intention. This empirical research supports the finding revealed by Rengiah and Sentosa (2016).…”
Section: Findings and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Accordingly, the position of both entrepreneurial motivation and entrepreneurial attitude is mediating variables that mediate between entrepreneurship education and entrepreneurial intention. This empirical research supports the finding revealed by Rengiah and Sentosa (2016).…”
Section: Findings and Discussionsupporting
confidence: 91%
“…Lee and Wong (2003) also uncovered that entrepreneurship education in higher education has a direct impact on forming students' attitudes in taking risks for the establishment of new businesses. In spite of this, research finding (Rengiah & Sentosa, 2016) revealed that entrepreneurial attitude mediates the relationship between entrepreneurship education and entrepreneurial intention.…”
Section: Introductionmentioning
confidence: 88%
“…Estimate the likelihood that you will start your own business in the foreseeable future it has crossed my mind to start a business of my own or with my partner, and do you plan to be self-employed in the foreseeable future? So far many researchers who use the concept of entrepreneurship intention among others, for examples Rantanena and Toikkob (2013), Remeikiene, Startiene, and Dumciuviene (2013), Douglas (2013), Gelderen et al, (2015) and Rengiah (2016).…”
Section: Entrepreneurial Intentionmentioning
confidence: 99%
“…This process has been implemented in various medium to higher education institutions in Indonesia. Entrepreneurship education has an important role in establishing and further intention to foster new business in a country (Paço, Ferreira, Raposo, Rodrigues, & Dinis, 2015a;Rengiah, 2016). Various studies indicate that the entrepreneurship education contribute to individual micro level and encourage the formation of the macro has a positive impact (Alhaji, 2015).…”
Section: Educationmentioning
confidence: 99%
“…Several statistical validity tests and analyses were then conducted, including reliability and composite reliability tests, validity tests using confirmatory factor analysis (CFA) for construct validity, discriminant validity for multicollinearity treatment, descriptive analysis, correlation, and structural equation modeling analysis. The steps in SEM analysis were CFA analysis, measurement model analysis of exogenous and endogenous constructs, discriminant analysis, composite reliability analysis and direct/ indirect impact analysis (mediating effect), and finally testing the goodness of fit for the hypothesized and generated model (Al-Jader & Sentosa, 2015;Rengiah & Sentosa, 2015).…”
Section: Cre4 Cre6mentioning
confidence: 99%